2013
DOI: 10.1017/s1368980013000050
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of trans-fat on labels of Brazilian food products

Abstract: Objective: The present study investigated how trans-fat is reported on the packaging of foods sold in a Brazilian supermarket. Design: The present descriptive, cross-sectional study analysed the ingredient list, nutrition facts label and claims of no trans-fat on the packaging. Setting: A large supermarket in Florianópolis, Brazil. Subjects: All food products available at the supermarket. Results: Of the 2327 study products, more than half had components containing trans-fat in the ingredient list, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 25 publications
4
38
0
6
Order By: Relevance
“…In addition, trans fat labelling in packaged foods are mandatory in Brazil [17,24]; and the presence of such fat in processed foods has been increasing [26]. Trans fat labelling is not mandatory in United Kingdom, but Roe et al [27] have shown a considerable decrease in the utilisation of trans fat by the British food industry.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, trans fat labelling in packaged foods are mandatory in Brazil [17,24]; and the presence of such fat in processed foods has been increasing [26]. Trans fat labelling is not mandatory in United Kingdom, but Roe et al [27] have shown a considerable decrease in the utilisation of trans fat by the British food industry.…”
Section: Discussionmentioning
confidence: 99%
“…The issues addressed by the stakeholders during the public consultation in Brazil have been raised in other publications about trans fat acids [11][12][13][14][15] , and should be taken into account. For example, stakeholders' concern regarding consumers' knowledge is an issue of considerable importance for the success of food labeling.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be seen that uncertainty about the presence of trans fat in a product can persist even after consumers read the product label information [56]. Danish documents also raise the issue of ingredient names that leave unclear whether or not a vegetable fat is hydrogenated [57].…”
Section: Resultsmentioning
confidence: 99%